Investment crowdfunding has little faith in sustainability! At least for the moment. Issue 1 (2nd January 2023) - Mendoza, Carmen; Parra Oller, Isabel María; Rezola, Álvaro; Suárez, Nuria
ABSTRACT: We analyze the influence of sustainability on the probability of achieving successful investment crowdfunding offerings. We use a sample of 1, 741 investment crowdfunding offerings launched by 1, 569 firms in the US during the period May 2016–September 2019 under the Form-C requirements of the JOBS Act. After accounting for potential endogeneity concerns affecting the degree of sustainability of each offering, results show that sustainability-related factors do not boost the chances of successful investment crowdfunding offerings. This result is not homogeneous across firms, operations, or financial environments. We obtain evidence on the influence of firm characteristics and on how offering affects the extent to which sustainability impacts success. Moreover, alternative funding sources and the market structure for funding portals also shape the influence of sustainability on offering success. Results are robust to considering both firm- and offering-level factors traditionally linked with success, as well as to different specifications of the econometric model, and to additional robustness tests.